Standard penetration test in Malaysia: Safety issues and improvement opportunities - Aishah, Abu Bakar; Nur Afifah Fatinnisa', Rizal Imran (Penerbit UMP, 2023)
Standard Penetration Test (SPT) is the most frequently used field test for site investigation where drilling work is performed in-situ to determine properties of geomaterials for a project. The SPT results can be affected by the ‘SPT System,’ which includes the operator of the drill rig, the specific model of the drill rig itself, the SPT equipment used to perform the test, and the procedures used in performing the overall test. The safety hazards associated with the system affect the SPT results. Although several countries are embracing innovative technologies in the SPT drilling works to enhance safety performance, the adoption of these technologies in Malaysia remains relatively sluggish. This study aims to analyse the current SPT practice in Malaysia from the lens of ‘the SPT System,’ technologies used in the SPT drilling works, and identify the best practice adopted locally in ensuring safety. This study collected 102 responses using a questionnaire survey validated by four construction professionals experienced in the SPT drilling works. The study revealed that the British Standards are the most used standards in Malaysia. The traditional methods are still being practiced as the “SPT System’ in Malaysia due to the difficulties in obtaining skilled operators for new technology adoption. Advanced technologies have not been adopted because construction professionals are complacent with the current technologies. Amongst innovative safety gear, smart equipment tags and smart wrist wearables are the most favourable. This study presents new findings and sheds light into the local practice of the construction professionals in Malaysia in the SPT drilling works. This study provides an insight for Malaysian construction industry to develop a strategy in improving the efficiency and safety of SPT drilling works through adoption of innovative technologies. Technology driven safety hazard mitigation may boost Malaysian Technical and Vocational Education and Training (TVET) industry and in doing so will increase TVET operators to be trained and certified.